Development of Enhanced Ultraviolet Resistance Hybrid Cotton Fabric using Functionalized Biocarbon derived from Teff (Eragrostis tef) Hay - Sahile, Kibebe; Prabhu, S. Venkatesa; Worku, Abebe (Asian Journal of Chemistry, 2023)
Due to the depletion of ozone atmosphere, there is a progressive increase in impact of ultraviolet (UV) radiation on human skin. The continual exposure of UV radiation results in serious adverse effects, such as photodermatosis, abnormal skin aging, erythema and skin cancer. Present study aimed to develop an improved UV resisting cotton fabric using the biocarbon derived from the abundantly available biomass residue of teff (Eragrostis tef) hay. The biocarbon had its surface functionalized, and then it was deposited onto the cotton using polyaniline as a grafting medium. In situ polymerization method was adopted for preparing the enhanced UV shielding fabric. The required functionalized biocarbon and polyaniline were optimized for attaining the maximum possible UV protection factor of the cotton. From the results, the UV protecting ability of the developed cotton fabric was found to be improved by 21 times higher as compared to ultraviolet protection factor (UPF = 66.3) than the original cotton (UPF = 3.1). In addition, the developed cotton fabric was observed to be exhibited excellent tensile strength. The morphological and structural studies were investigated using scanning electron microscopy and Fourier transform infrared spectroscopy for pure cotton fabric and hybrid material coated by biocarbon. Experimentation results revealed that the biocarbon obtained from teff hay could be a used for developing the enhanced UV protecting textile material. Hence, the acquired material can perform for better ultraviolet protection.